Characteristics and outcomes in a prospective cohort of patients with histologically diagnosed aortitis - Goldhar, Hart A.; Walker, Kyle M.; Abdelrazek, Mohamed; Belanger, Eric C.; Boodhwani, Munir; Milman, Nataliya (Oxford University Press (OUP), 2019)
Objectives Our aim was to evaluate characteristics and prospective adverse aortic outcomes in a cohort of patients with non-infectious histological aortitis. Methods Patients with histological aortitis, diagnosed at the Ottawa Hospital after surgical repair of thoracic aortic aneurysms or dissections, consented to enrolment in a prospective observational cohort. Patients were assessed for an underlying inflammatory condition and followed prospectively with periodic clinical, laboratory and radiographic assessments. Aortic outcomes during follow-up included significant events, defined as new thoracic or abdominal aortic aneurysms, dissections, ruptures or other complications requiring aortic intervention, in addition to aortic branch ectasias, aneurysms and stenosis. Results Sixteen patients with histological aortitis from surgical procedures performed between 2010 and 2017 were included; nine had idiopathic and seven had secondary aortitis. Idiopathic patients were more likely to have smoked (100 vs 43%, P = 0.02) and had more associated arch or descending aortic aneurysms on pre-operative baseline imaging compared with secondary aortitis (6 vs 0, P = 0.01). At the median 3.6 years of follow-up, eight patients (50%) had 10 significant aortic events. The incidence of aortic dissection was higher in the first year post-surgery, compared with subsequent years, whereas incident aneurysms occurred throughout follow-up. Elevated inflammatory markers during follow-up trended towards association with accumulation of severe aortic damage. Conclusion This is the first reported prospective study in patients with histological aortitis. Within the limitations of a small cohort, we report a high incidence of aortic complications. Studies with a larger sample size and longer follow-up are needed to corroborate these findings.
Keywords: Vasculitis; Giant cell arteritis; Temporal arteritis; Other idiopathic inflammatory disorders; Cardiovascular